Evaluation of different agricultural biomass for bioethanol production - Bansal, Sunil (Kansas State University, 2010)
In our study, five different bioenergy crops: wheat straw (Triticum aestivum), forage sorghum stover (sorghum bicolor), switchgrass (Panicum virgatum), miscanthus (Miscanthus giganteus) and sweet sorghum baggase (Sorghum bicolor) were evaluated for bio-ethanol production at 20% (w/v) initial substrate concentration under separate hydrolysis and fermentation (SHF) process. The substrates were ground to pass through 600µm mesh size and treated with 2% (w/v) NaOH at 121oC for 30 minutes. The washed and neutralized pretreated residues were subjected to saccharification using cellulase and β-glucosidase enzymes (ratio 1:1.25) at concentrations of 25 filter paper unit (fpu)/g and 31.25fpu/g, respectively, in pH 5.0 citrate buffer in an orbital incubator shaker at 150 rpm for 72 h. The hydrolysate obtained was centrifuged and supernatant was collected for fermentation. Fermentation was performed in shake flasks using Saccharomyces cerevisiae at 10% (w/v) inoculum concentration at 100 rpm for 24 h. Alkali treatment was effective in delignification of all the biomass feedstocks. The highest percent removal on raw biomass basis was attained for sorghum stover BMR-DP (81.3%, w/w) followed by miscanthus (79.9%, w/w), sorghum stover BMR-RL (69.2 %, w/w), wheat straw (68.0 %, w/w), switchgrass (66.0%, w/w), and sorghum baggase (65.4%, w/w). Glucan saccharification varied from 56.4-72.6 % (w/w) corresponding to a glucose levels of 0.45-0.34 g/g of dry substrate. Highest saccharification was observed for wheat straw while lowest was observed for miscanthus after 48 hours of hydrolysis. A maximum final ethanol concentration of 4.3% (w/v) was observed for wheat straw followed by sorghum baggase (4.2%), sorghum RL-BMR (3.6%), miscanthus (3.4%), sorghum DP-BMR (3.4%), and switchgrass (3.2%). From our studies, it is evident that high substrate concentration used for enzymatic hydrolysis was able to provide high final ethanol concentration. The lignin content and its arrangement in different biomass feedstocks may have affected saccharification and subsequent ethanol production. Bulk density and flowability are the two major key parameters that should be addressed to reduce processing cost of biomass for bioethanol production. Pelleting of biomass can increase the bulk density, thereby reducing the handling and transportation costs. In addition to above study, I analyzed the changes in chemical composition due to pelletization and pretreatment, and its effect on ethanol production by comparing unpelleted and pelleted biomass ethanol production efficiency. Wheat straw and big bluestem pelleted and unpelleted biomass were compared for their ethanol production efficiency. Pelleted and unpelleted wheat straw (Triticum aestivum) and bigblue stem (Andropogon gerardii Vitman) at a substrate concentration of 10% (w/v) were subjected to 2% NaOH treatment at 1210C for 30 min and the resulting residues were analyzed for changes in chemical composition. Saccharification of residue was done at substrate concentration of 12% (w/v) for 48 h. The sugars obtained were fermented to ethanol using Saccharomyces cerevisiae. Pelletization did not significantly affect the chemical composition of biomass in terms of glucan, xylan and lignin content. Delignification of pelleted biomass was greater than unpelleted biomass. Pelletization did not influence final ethanol production for both substrates.
Keywords: Bioethanol; Biomass; High solid saccharification; Effect of pelleting; Alkali pretreatment; Energy (0791)